General care in the management of severe traumatic brain injury: Latin American consensus - Godoy, D. A.; Videtta, W.; Santa Cruz, R.; Silva, X.; Aguilera-Rodriguez, S.; Carreno-Rodriguez, J. N.; Ciccioli, F.; Pinero, G.; Ciro, J. D.; Re-Gutierrez, S.; Domeniconi, G.; Fischer, D.; et al. (My University, 2020)
Severe traumatic brain injury (sTBI) remains prevalent in the young adult population. Indeed, far from descending, the incidence of sTBI remains high. One of the key bases of treatment is to avoid, detect and correct secondary injuries of systemic origin, which aggravate the primary lesion. Much of this can be achieved by maintaining an adequate physiological microenvironment allowing recovery of the damaged brain tissue. General care measures are nonspecific actions designed to meet that objective. The available guidelines on the management of sTBI have not included the topics contemplated in this consensus. In this regard, a group of members of the Latin American Brain Injury Consortium (LABIC), involved in the different aspects of the acute management of sTBI (neurosurgeons, intensivists, anesthesiologists, neurologists, nurses and physiotherapists) were gathered. An exhaustive literature search was made of selected topics in the LILACS, PubMed, Embase, Scopus, Cochrane Controlled Register of Trials and Web of Science databases. To establish recommendations or suggestions with their respective strength or weakness, the GRADE methodology (Grading of Recommendations, Assessment, Development and Evaluation) was applied. Additionally, certain recommendations (included in complementary material) were not assessed by GRADE, because they constitute a set of therapeutic actions of effective compliance, in which it was not possible to apply the said methodology. Thirty-two recommendations were established, 16 strong and 16 weak, with their respective levels of evidence. This consensus attempts to standardize and establish basic general care measures in this particular patient population. (c) 2020 Elsevier Espana, S.L.U. y SEMICYUC. All rights reserved.
Keywords: traumatic brain injury; consensus; secondary injury; general care; homeostasis; physiological neuroprotection